Analyzing Pakistan’s national curriculum textbooks in religious-based construction and demonisation of ‘other’ for high schools - Jan, Qasim (British Journal of religious education, 2025)
This study analysis the role of Pakistan’s National Curriculum textbooks in normalising religious-based construction and demonisation of the ‘other’. Specifically, it examines textbooks issued by Federal Textbook Board for high school students using thematic content analysis. The research aims to investigate the portrayal of religious-based construction and demonisation of the ‘other’ in sample textbooks projected ‘legitimate knowledge’ across various subjects. In addition, it also analyzes that how the textbooks deviate from their supposed educational purpose to serve the vested interested of the ruling elites. The analysis employs a theoretical framework based on Apple’s concept of ‘legitimate knowledge’, and N. Kalyvas and Frankfurter’s notion of the ‘normalisation of violence’ as both a process and an outcome. By employing this theoretical framework, the study reveals that the presentation of ‘legitimate knowledge’ in textbooks plays a crucial role in normalising religious-based construction and demonisation of the ‘other’ by depicting them as enemies, spies, cruel, uncivilised, hypocritical, and deserving severe punishment. Furthermore, the textbooks construct binary structures such as ‘Believers/Muslims vs. Non-believers/non-Muslims’, portraying various groups in a hostile manner. The analysis also sheds light on the factors influencing the textbooks’ role, which primarily serves the strategic and political interests of the Pakistani state, particularly during post-9/11 which significantly contributed to regional violence.